Formulasi Tablet Mukoadesif Ekstrak Etanol Daun Mangga Bapang (Mangifera indica L. ‘Bapang’) sebagai Antidiabetes Menggunakan Matriks Guar Gum - LIA NADIA FITHRIYANI; DHADHANG WAHYU K; EKA PRASASTI NUR R (JURNAL ILMU KEFARMASIAN INDONESIA, 2014)
Ethanolic extract of mango’s leaves variety of bapang (Mangifera indica L. ‘Bapang’) has been known to contains mangiferin which has antidiabetic activity in patients with diabetes mellitus. This study aimed to obtain a formulation of tablets of ethanolic extract mango leaves with variety of bapang with good physical characteristic and know the effect of variations concentration of guar gum on the properties of mucoadhesive. Tablets were prepared using wet granulation method varying levels of guar gum as a bioadhesive matrix. Tablets were tested physical characteristics and mucoadhesive strength in vitro by using a rotating cylinder and observed within 8 hours. The results showed that the tablets of ethanolic extract mango leaves with variety of bapang have good physical characteristics. The result of mucoadhesive in vitro test showed that all formulas have good mucoadhesive strength. Mucoadhesive strength increased with the increase in the concentration of guar gum. The result of this research showed that the tablets of formula 4 with the highest concentration of guar gum showed the best mucoadhesive strength where they could be attach of 7 ± 1 hour.